Topological surface states of Bi2Se3 coexisting with Se vacancies - Yan, Binghai; Zhang, Delin; Felser, Claudia (Physica Status Solidi-Rapid Research Letters, 2013)
Although topological surface states are known to be robust against nonmagnetic surface perturbations, their band dispersions and spatial distributions are still sensitive to surface defects. Taking Bi2Se3 as an example, we demonstrate that Se vacancies modify the surface band structures considerably. When large numbers of Se vacancies exist on the surface, topological surface states may sink down from the first to the second quintuple layer and get separated from the vacancies. We simulated scanning tunnelling microscopy images to distinguish surfaces with Se and Bi terminations. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: BiSe; First-principles calculations; Se; STM; Vacancies